Speech-to-text reporting - appropriate form of support for education, work and participation in social and cultural life of the deaf and hard of hearing persons - Ewa Domagała-Zyśk (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
This article presents speech-to-text reporting as an adequate form of support for education, work and full participation in social and cultural life of the deaf and hard of hearing. This form of support is known in Western Europe since the 80s of the twentieth century. However, there are a lot of discussions nowadays as for its  scope and financing as well as the most effective forms of precise speech recording. The article discusses different types of speech-to-text reporting, shows the rules for creating the recordings and points out the advantages and difficulties of using this service.